“DESA SEHAT BERDAYA” Inovasi Kesehatan & Ekonomi Lokal Berbasis Digital - Intan Yulia Lestari; Muhammad Iklil Fauzan Kohongia; Sriwandi Junaidi; Fathia Nur Mawaddah Uno; Dewi Anggraini A. Latoko; Ranisa Rahman; Anisa Canon (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
The "Desa Sehat Berdaya: Digital-Based Health and Local Economy Innovation" program was implemented in Bulawan 2 Village to address low awareness of preventive health, Clean and Healthy Living Behaviors (PHBS), and limited social education for children and adolescents on bullying, early marriage, and drug abuse (NAPZA). The goal was to improve public health through promotive-preventive interventions, enhance health cadre capacity for sustainable village programs, and increase understanding of healthy behaviors and social risks among youth. A participatory-collaborative approach was used, involving community organization, multi-party coordination, program presentation, intervention implementation, evaluation, and follow-up with health cadres, alongside simple digital media utilization. Results showed increased community participation in posyandu, healthy exercises, and free health checkups, as well as improved cadre capacity through MP-ASI training. For youth, PHBS socialization, anti-bullying, early marriage education, and NAPZA awareness enhanced understanding of healthy behaviors and social issues. Collaboration with Karang Taruna strengthened youth participation and social cohesion.